2008
DOI: 10.1007/s10875-008-9270-8
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Life of Children and Adolescents with X-Linked Agammaglobulinemia

Abstract: The agammaglobulinemia subjects perceived a lower global quality of life than the healthy subjects, but significantly higher than the rheumatic diseases controls. The clinical relevance of health-related quality of life assessment in X-linked agammaglobulinemia pediatric patients is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
1
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 9 publications
4
27
1
3
Order By: Relevance
“…Considering that HRQOL data provide direct information about the impact of a disorder and its treatment, HRQOL assessments could be a part of multimodal assessment and treatment approach in children with PID as well. However, the evidence of to what extent PID affects HRQOL in children is limited, because only three studies that evaluated HRQOL in this population are available 1416…”
Section: Introductionmentioning
confidence: 99%
“…Considering that HRQOL data provide direct information about the impact of a disorder and its treatment, HRQOL assessments could be a part of multimodal assessment and treatment approach in children with PID as well. However, the evidence of to what extent PID affects HRQOL in children is limited, because only three studies that evaluated HRQOL in this population are available 1416…”
Section: Introductionmentioning
confidence: 99%
“…El PedsQL es el cuestionario que ha sido más utilizado en niños con diagnóstico de inmunodeficiencias primarias. [20][21][22][23][24][25][26][27][28] Existen algunos reportes, la gran mayoría de ellos en ensayos clínicos, en los que se ha utilizado para comparar dos o más tratamientos, pero hay muy poca información a escala mundial de la calidad de vida en las inmunodeficiencias primarias y es nula en el caso de nuestro país.…”
Section: Discussionunclassified
“…Modelos lineales para estimar el efecto del retraso de diagnóstico de inmunodeficiencia primaria en niños sin y con complicación pulmonar en Italia y se comparó con niños sanos y con pacientes con enfermedades reumatológicas, se reportó una calidad de vida menor en los pacientes con enfermedades reumatológicas (72.1 puntos), seguida por la de pacientes con agammaglobulinemia (75.8 puntos), en comparación con los niños sanos (86.8 puntos); hubo una asociación significativa entre la percepción de los pacientes y la de los padres. 25 A diferencia de otras enfermedades crónicas como el asma o la diabetes en las inmunodeficiencias primarias, a pesar de que son afecciones crónicas y que frecuentemente ya tienen complicaciones al momento del diagnóstico, no es común encontrar informes de calidad de vida; salvo en algunos ensayos clínicos que comparan opciones de tratamiento sustitutivo. Debido a que los pacientes incluidos en el estudio ya estaban diagnosticados y en tratamiento no contamos con una medición de la calidad de vida basal; es decir, antes del inicio del tratamiento o en el momento del diagnóstico (aunado a que sólo realizamos una medición de calidad de vida para cada paciente).…”
Section: Discussionunclassified
“…[18] In 2003 Porpiglia et al [19] reported successful long lasting donor B-cell engraftment using HCT in two murine models of B-cell deficiency without administration of irradiation or myelotoxic drugs. These findings suggest that it may not be necessary to make “space” in the bone marrow to achieve sufficient engraftment.…”
Section: Discussionmentioning
confidence: 99%